2017
DOI: 10.15675/gepros.v12i2.1644
|View full text |Cite
|
Sign up to set email alerts
|

A review of the soft side in project management: concept, trends and challenges

Abstract: Our aim is to analyze the changes that have taken place in the academic literature of project management induced by the growing interest in the soft side within project management, identifying concepts, trends and challenges. Based on a bibliometric approach, a systematic literature review focusing on content analysis was made in articles published from 1994 to 2015 in the ISI Web of Science and Scopus databases. The literature was found to maintain the separation between the hard and the soft side, being the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In her review of generic qualities that are most valued by employers, Cicekli [55] determined that many of the skills sought by employers are generic or soft skills. These skills include communication, interpersonal and persuasive, and teamwork skills, time management, flexibility and the ability to deal with ambiguity and change, motivation, ownership and sense of achievement, organizational effectiveness, and leadership skills [48], [55]- [58].…”
Section: Need For Soft Skills As Well As Project Management Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…In her review of generic qualities that are most valued by employers, Cicekli [55] determined that many of the skills sought by employers are generic or soft skills. These skills include communication, interpersonal and persuasive, and teamwork skills, time management, flexibility and the ability to deal with ambiguity and change, motivation, ownership and sense of achievement, organizational effectiveness, and leadership skills [48], [55]- [58].…”
Section: Need For Soft Skills As Well As Project Management Skillsmentioning
confidence: 99%
“…These needed competencies encompass not only the technical competence, but also contextual competence, addressing the context of the project and organization, and behavioral competence, relating to those soft skills and leadership skills necessary for project success [61], [47], [1], [44]. Azim et al [56] argue that the importance of people aspects of projects and the underlying soft skills are essential for project success, while another study [58] concluded that soft skills have more influence on projects' success than do technical skills.…”
Section: Need For Soft Skills As Well As Project Management Skillsmentioning
confidence: 99%
“…The bibliometric approach is particularly useful for large sample sizes since it focuses on metrics based on the number of publications and the metadata. On the other hand, the content analysis focuses on an in-depth review of the sample but allows analytical flexibility (Durão et al, 2017;Duriau et al, 2007). These approaches are used to probe the existing literature and identify relevant patterns, works, and authors of the particular field of research, and investigate the evolution of the publications stratified by journals (Durão et al, 2017).…”
Section: Methodsmentioning
confidence: 99%